China and the Global Economy - Lin, Justin Yifu (Taylor and Francis, 2013)
As a result of the extraordinary performance in the past 20 years, China's status in the global economy has dramatically changed. In this article, I reflect on China's unprecedented growth, examine the reasons for that growth, and discuss promising prospects for the Chinese economy to maintain an 8% annual growth rate in the coming two decades. Although to maintain that growth rate, China will definitely encounter many challenges – both internally and externally. The twenty-first century has witnessed the emergence of a multi-polar growth world, with many of the new growth poles being emerging market economies. China has become the top contributor to global GDP growth in the decade of 2000–2009. If China copes appropriately with its challenges and deepens its structural reforms, it has the potential to continue its role as a leading power in supporting a multi-polar global economic architecture that benefits both developing and high-income countries in various ways.